2017
DOI: 10.4401/ag-7362
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Complex Fluids with Smoothed Particle Hydrodynamics

Abstract: Complex fluid dynamics encompasses a large variety of flows, such as fluids with non-Newtonian rheology, multiphase and multi-fluid flows (suspensions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…The inlet will also give advantage in terms of performance and robustness. In fact, the high viscosity values that will be involved in BM4 require the adoption of the semi implicit integration scheme, recently introduced in GPUSPH [Zago et al, 2018]; in that case, we shown that the performances of the semi implicit scheme have a strict dependence on the number of particles involved in the simulation, then simpler geometries obtained substituting the piston structure with an open boundary will be more suited for the adoption of the semi implicit scheme.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The inlet will also give advantage in terms of performance and robustness. In fact, the high viscosity values that will be involved in BM4 require the adoption of the semi implicit integration scheme, recently introduced in GPUSPH [Zago et al, 2018]; in that case, we shown that the performances of the semi implicit scheme have a strict dependence on the number of particles involved in the simulation, then simpler geometries obtained substituting the piston structure with an open boundary will be more suited for the adoption of the semi implicit scheme.…”
Section: Discussionmentioning
confidence: 93%
“…The dynamical equations seen above are discretized according to the SPH method as described in , Hérault et al [2011] and Zago et al [2018] obtaining: 8for the continuity Equation 1, 9for the momentum Equation 2, and 10for the thermal Equation 3.…”
Section: Sph Discretization Of the Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We will make extensive reference to our experience from the implementation of GPUSPH [13][14][15][16][17], the first implementation of SPH to run completely on GPU using CUDA and currently supporting multi-GPU and multi-node distribution of the computation. However, all the themes that we discuss and solutions we present are of interest to all particle systems and related methods, regardless of the specific theoretical background underlying them.…”
Section: Introductionmentioning
confidence: 99%